Carbon ion radiotherapy decreases the impact of tumor heterogeneity on radiation response in experimental prostate tumors. Issue 2 (10th August 2016) - Glowa, Christin; Karger, Christian P.; Brons, Stephan; Zhao, Dawen; Mason, Ralph P.; Huber, Peter E.; Debus, Jürgen; Peschke, Peter
Highlights: Compared to the same photon dose, carbon ions are generally more effective. In tumors, the effect of carbon ions relative to photons increases with grading. Therapeutic response to carbon ion therapy is less heterogeneous than for photons. Carbon ions override most conventional tumor-associated factors of radioresistance. Abstract: Objective: To quantitatively study the impact of intrinsic tumor characteristics and microenvironmental factors on local tumor control after irradiation with carbon ( 12 C-) ions and photons in an experimental prostate tumor model. Material and Methods: Three sublines of a syngeneic rat prostate tumor (R3327) differing in grading (highly (-H) moderately (-HI) or anaplastic (-AT1)) were irradiated with increasing single doses of either 12 C-ions or 6 MV photons in Copenhagen rats. Primary endpoint was local tumor control within 300 days. The relative biological effectiveness (RBE) of 12 C-ions was calculated from the dose at 50% tumor control probability (TCD50 ) of photons and 12 C-ions and was correlated with histological, physiological and genetic tumor parameters. Results: Experimental findings demonstrated that (i) TCD50 -values between the three tumor sublines differed less for 12 C-ions (23.6–32.9 Gy) than for photons (38.2–75.7 Gy), (ii) the slope of the dose-response curve for each tumor line was steeper for 12 C-ions than for photons, and (iii) the RBE increased with tumor grading from 1.62 ± 0.11 (H) to 2.08 ± 0.13 (HI) to 2.30 ± 0.08 (AT1). Conclusion: The response to 12 C-ions is less dependent on resistance factors as well as on heterogeneity between and within tumor sublines as compared to photons. A clear correlation between decreasing differentiation status and increasing RBE was found. 12 C-ions may therefore be a therapeutic option especially in patients with undifferentiated prostate tumors, expressing high resistance against photons.